A Multivariate EWMA Control Chart with fuzzy approach for multinomial variables. (LACCEI, 2024)
The aim of this paper is to improve the response of the Multivariate Multinomial Fuzzy T2 control chart to detect small shifts by the implementation of a MEWMA control chart. In this research a multivariate control chart based on the MEWMA chart is proposed to improve the sensitivity to detect small shifts in the vector of means of the T2 chart with fuzzy approach presented in the literature, to deal with p correlated multinomial multivariate variables. The parameters for the chart are obtained from historical data and the control limits by simulation. The performance of the new chart proposed is compared with the performance of the T2 control chart through the Average Run Length (ARL) value. The performance of this new chart can be obtained through a program developed by the authors.